Revision of the genus Melanagromyza in California, with descriptions of three new species (Diptera: Agromyzidae) - Shi, Li; Gaimari, Stephen D. (Zootaxa, 2015)
The 27 Californian species of the genus Melanagromyza Hendel (Diptera: Agromyzidae) are reviewed, including descriptions of three new species (Melanagromyza californiana sp. nov., M. chemsaki sp. nov. and M. gonzalesina sp. nov.) and the first record for one species (Melanagromyza martini Spencer) for California and the USA. All species in California are described or redescribed, with illustrations and photographs, and a key to the species is presented. Maps for the species in California, along with host distributions, are provided, with comments on biology and host plants.